PEMIJAHAN IKAN LELE SANGKURIANG (Clarias gariepinus) DENGAN DOSIS YANG BERBEDA DI AQUACULTURE FARM RIMBO BUJANG KABUPATEN TEBO PROVINSI JAMBI - Sri Maryeni; Rini Hertati; Juliana Juliana (Universitas Muara Bungo, 2022)
Sangkuriang catfish (Clarias sp.) is a type of fish that is widely cultivated and has afairly profitable economic value. Spawning activities are carried out in order to achieve the desired production target, but spawning results do not always produce productionwith the expected results. This study aims to determine the procedure for spawning and to determine the response of sangkuriang catfish with different doses during spawning.The survey method was used with direct observation in the field. The results showed thatthe semi-natural sangkuriang catfish spawning process consisted of: pond preparation, broodstock selection, broodstock weighing, hormone injection, spawning and larvalcare. Meanwhile, the response of sangkuriang catfish given different doses during spawning was giving different percentages of weight loss. A dose of 0.5 ml gave amaximum egg production of 0.4%, while a dose of 0.25 ml gave good hatchabilityaccording to field observations of 85%.